Congratulations to Yat Sum Ho from Cambourne Village College for successfully solving this problem!
i)
Assume that can be written in the form of
, which will allow us to write it as
=
.
If this is true, = 3 and
=
Having and
satisfy these two equations, which yields
=
ii)
To begin with, we can factor out a 2 from this square root, giving us
The inner square root looks quite similar to part (i), so it is reasonable to try approach it with the same strategy.
=
.
Having and
satisfies
= 3 and
This means that our original expression